Correlation between the in-plain substrate strain and electrocatalytic activity of strontium ruthenate thin films in dye-sensitized solar cells. Issue 28 (29th June 2016) - Liu, Tao; Hou, Juan; Wang, Bing; Bai, Feiming; Chen, Haijun; Gao, Lei; Cao, Yonghai; He, Hongcai; Wang, Jinshu; Wang, Ning; Cao, Guozhong; Guo, Zhanhu
Abstract : Solar cells with a SRO/MAO counter electrode show an increased PCE compared to those with SRO/STO due to in-plane tensile strain. Abstract : Perovskite strontium ruthenate (SrRuO3, i.e., SRO) films, for the first time serving as a Pt-free counter electrode in dye-sensitized solar cells (DSSCs), have demonstrated promising electrocatalytic activity towards triiodide (I3 − ) reduction, resulting in power conversion efficiency (PCE) close to that of conventional Pt counter electrodes. Furthermore, the lattice mismatch with the substrate could change the electrocatalytic activity of epitaxial SRO films, arising from the deviations from the local symmetry. X-ray diffraction (XRD) results confirm that in-plain tensile strain induces lattice shortening along the out-of-plane direction for the SRO film deposited on a (100) oriented MgAl2 O4 (MAO) single crystal substrate (SRO/MAO), whereas biaxial compressive strain in the plane of SRO grown on a (100) oriented single crystal SrTiO3 (STO) substrate (SRO/STO) leads to the elongation of out-of-plane spacing. Our results show that the SRO/MAO counter electrode exhibits an improved electrocatalytic activity, reduced charge-transfer resistance ( R ct ) at the counter electrode/electrolyte interface, and accelerated I3 − diffusion in the electrolyte compared to the SRO/STO counter electrode. The decreased Ru–I3 − distance perpendicular to the surface upon application of in-plane tensile strain would contribute to the increased adsorption strength of the I3 −, and thus promoted the I3 − /I − redox reaction. Hence, the device with the SRO/MAO counter electrode reveals an increase of 17.18% in PCE compared to the SRO/STO based device. This work provides new insight into further enhancement of PCE through design and engineering of the crystal and microstructure of SRO films, which is applicable to a range of perovskite chemistries.